Pengaruh Bentuk Bangunan Terhadap Pola Tatanan Ruang pada Beachwalk Shopping Center Bali - Rahim, Putri Adelia Purwidya; Subiyantoro, Heru (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Today the development of shopping malls in Indonesia has various concepts that are carried to attract visitors. Beachwalk Shopping Center located in Kuta, Bali is one of the malls that carries the concept of citywalk. The unique shape of the mass of the Beachwalk Shoppping Center building has its own meaning. The shape of the mass order of the building that affects the pattern of spatial order. The purpose of this study was to determine the pattern of spatial order formed in Beachwalk Shopping Center. This study used an intrepretative qualitative approach with descriptive data presentation. The finding in this study is that the shape of the mass organically forms a curved linear space organization with the outdoor area as the center, forming a linear path configuration. The linear path configuration applied by the mall is very effective to make visitors surround all parts of the mall. But at some point the branching can confuse visitors who are not familiar with the spatial arrangement of the mall.